Exploring the Association Between Genetic Polymorphisms in Genes Involved in Craniofacial Development and Isolated Tooth Agenesis - Küchler, Erika Calvano; Reis, Caio Luiz Bitencourt; Silva-Sousa, Alice Corrêa; Marañón-Vásquez, Guido Artemio; Matsumoto, Mirian Aiko Nakane; Sebastiani, Aline; Scariot, Rafaela; Paddenberg, Eva; Proff, Peter; Kirschneck, Christian (Frontiers in Physiology, 2021)
Tooth agenesis is a common congenital anomaly in humans and is more common in oral cleft patients than in the general population. Many previous studies suggested that oral cleft and tooth agenesis share a similar genetic background. Therefore, this study explored the association between isolated tooth agenesis and genetic polymorphisms in genes that are crucial for craniofacial and tooth development. Panoramic radiographs, anamnesis and genomic DNA from 273 patients were included. Patients were classified as tooth agenesis present, when at least one permanent tooth was congenitally missing. Patients with syndromes and oral cleft were excluded. Only unrelated patients were included. The genetic polymorphisms in BMP2 (rs235768 and rs1005464), BMP4 (rs17563), RUNX2 (rs59983488 and rs1200425) and SMAD6 (rs3934908 and rs2119261) were genotyped by real-time Polymerase Chain Reaction. Genotype and allele distributions were compared between the tooth agenesis phenotypes and controls by chi-square test. Haplotype and diplotype analysis were also performed, in addition to multivariate analysis (alpha of 0.05). A total of 86 tooth agenesis cases and 187 controls were evaluated. For the rs235768 in BMP2, patients carrying TT genotype have higher chance to present tooth agenesis (p <0.001; Prevalence Ratio [PR] = 8.29; 95% Confidence Interval [CI] = 4.26 – 16.10). The TT genotype in rs3934908 (SMAD6) was associated with higher chance to present third molar agenesis (p= 0.023; PR= 3.25; 95% CI= 1.17 – 8.99). BMP2 was also associated in haplotype and diplotype analysis with tooth agenesis. In conclusion, genetic polymorphisms in BMP2 and SMAD6 were associated with isolated tooth agenesis.